PENGARUH KOMITMEN ORGANISASI, JOB INSECURITY DAN DISIPLIN KERJA TERHADAP TURNOVER INTENTION KARYAWAN OUTSOURCING PADA PT. TIGA JANGKAR UTAMA DEPOK - Winari Radisya; Machasin Machasin; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of organizational commitment, job insecurityand work discipline on the turnover intention of outsourcing employees at PT. TigaJangkar Utama. In this study, data collection was carried out by distributingquestionnaires using the proportional stratified random sampling method. Thepopulation in this study were outsourced employees of PT. Tiga Jangkar Utamawith a sample of 99 employees. While the data analysis used is multiple linearregression analysis with SPSS 22 tools.Based on the results of the analysis, it wasfound that simultaneously organizational commitment, job insecurity and workdiscipline had a significant effect on turnover intention. Organizationalcommitment has a negative and significant effect on turnover intention. Jobinsecurity has a positive and significant effect on turnover intention. And workdiscipline has a negative and significant effect on turnover intention. With acoefficient of determination of 0.634 which means organizational commitment, jobinsecurity and work discipline have an influence of 63,4% on the Turnoverintention of outsourcing employees, while the remaining 36.6% describes otherindependent variables not observed in this study. Keywords: Organizational commitment, job insecurity , work discipline andturnover intention